The modulation of leaf metabolism plays a role in salt tolerance of Cymodocea nodosa exposed to hypersaline stress in mesocosms - Piro, Amalia; Marín-Guirao, Lázaro; Serra, Ilia A.; Spadafora, Antonia; Sandoval-Gil, José M.; Bernardeau-Esteller, Jaime; Fernandez, Juan M. R.; Mazzuca, Silvia (Frontiers in Plant Science, 2015)
By the proteomic approach we tested the physiological responses of the euryhaline seagrass Cymodocea nodosa to deliberate manipulation of salinity in a mesocosm system. Plants were subjected to a chronic hypersaline condition (43 psu) to compare their proteins expression and plant photochemistry responses after 15 and 30 days of exposure with those of plants cultured under normal/ambient saline conditions (37 psu). Results showed a general decline in the expression level of leaf proteins in hypersaline stressed plants, with more intense reductions on the long-lasting exposure. Specifically, the carbon-fixing enzyme RuBisCo displayed a lower expression level in stressed plants relative to controls; while contrarily, the key enzymes involve in the regulation of glycolisis, the cytosolic glyceraldehyde-3-phopsphate dehydrogenase, the enolase 2 and triose-phosphate isomerase, showed significant higher expression levels. Responses that suggest a shift of the carbon metabolism in stressed plants. Hypersaline stress also induced a significant alteration of the photosynthetic physiology of the C. nodosa by means of the down-regulation of structural proteins and enzymes of both PSII and PSI; however we found an over-expression of the cytochrome b559 alpha subunit of the PSII initial complex, which is a receptor for the PSII core proteins involved in biogenesis or repair processes and therefore potentially involved in the absence of effects at the photochemical level of stressed plants. As expected hypersalinity also affects the vacuolar metabolism increasing the leaf cell turgor pressure and enhancing the up-take of Na+ by the over-expression of the tonoplast specific intrinsic protein pyrophosphate-energized inorganic pyrophosphatase (H(+)-PPase) that is coupled with the Na+/H+-antiporter. The modulation of carbon metabolism and the enhancement of vacuole capacity in Na+ sequestration and osmolarity changes are discussed in relation to salt tolerance of C. nodosa.